2018
DOI: 10.2147/shtt.s152018
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the role of telemedicine in the management of Parkinson’s disease

Abstract: Parkinson's disease (PD) is a progressive neurological disorder that primarily affects older adults. The number of patients who receive specialty care continues to be limited, even though the benefits of seeing a movement disorder specialist for management of PD have been well established. Telemedicine has been suggested as a useful tool in addressing the problem of access to specialty care. As evidenced by the literature, it has been suggested that using telemedicine to treat PD is feasible and economically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…The application (Zoom) currently used was easily used by the patients with a short time of setting up; however, delayed audio connection at the time of logging in was a common technical challenge. The current study showed time and cost saving similar to that in previous studies (2,5). Despite less money being saved as compared to that in other studies, due to the depreciation of the local currency and the fact that most patients lived in the same governorate (68.4%), the money saved was substantial for the patients, given their low socioeconomic level.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The application (Zoom) currently used was easily used by the patients with a short time of setting up; however, delayed audio connection at the time of logging in was a common technical challenge. The current study showed time and cost saving similar to that in previous studies (2,5). Despite less money being saved as compared to that in other studies, due to the depreciation of the local currency and the fact that most patients lived in the same governorate (68.4%), the money saved was substantial for the patients, given their low socioeconomic level.…”
Section: Discussionsupporting
confidence: 79%
“…This study included ideal aspects of telemedicine, such as easy-to-use technology, combined use of synchronous and asynchronous programs, and previous in-person visits. However, other aspects, such as the use of high-resolution devices, support by technology experts, and high-speed Internet connectivity, were inadequate (2,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular, consistent follow-up visits are possible through telemedicine without the need for the patient to travel and are associated with an increased sense of security and comfort for the patient by allowing him or her to remain at home. 54 Behavioral health follow-up visits, particularly those to ensure medication adherence or discuss medication adjustments, have been successfully conducted virtually. 55 Virtual follow-up visits may also be associated with a lower no-show rate, in relation to in-person follow-up visits.…”
Section: Treating and Monitoring Patients With Pdp Or Drp During Tele-visitsmentioning
confidence: 99%